Screening of the chemical reactivity of three different graphite sources using the formation of reductively alkylated graphene as a model reaction - Knirsch, Kathrin; Englert, Jan; Dotzer, Christoph; Hauke, Frank; Hirsch, Andreas; Hauke, Frank (Chemical Communications, 2013)
Reductive alkylation of three graphite starting materials G(flake), G(powder), and G(spherical) reveals pronounced differences in the obtained covalently functionalized graphene with respect to the degree of functionalization, exfoliation efficiency and product homogeneity, as demonstrated by statistical Raman microscopy (SRM), TGA/MS, IR-spectroscopy and solubility behavior.This journal is © The Royal Society of Chemistry 2013.